2011
DOI: 10.1080/17480930.2011.623830
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vegetation cover on temperature and humidity properties in the reclaimed area of a brown coal dump

Abstract: Vegetation cover of the landscape plays an important role in the transformation of solar energy and the formation of microclimate in the landscape. A study carried out in the Velka´podkrusˇnohorska´brown coal dump (Czech Republic) focused on the impact of the structure and functions of landscape cover on temperature and humidity properties in nine localities with various states of vegetation cover. The development of temperature and relative humidity measured in various levels (temperature and relative humidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
9
0
2
Order By: Relevance
“…Vegetation structure can also influence the temperature, humidity, and air flow near the woodland floor [ 27 , 28 , 29 ]. These variables are often examined in tick population studies because they have been shown to affect tick survival and questing behavior [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation structure can also influence the temperature, humidity, and air flow near the woodland floor [ 27 , 28 , 29 ]. These variables are often examined in tick population studies because they have been shown to affect tick survival and questing behavior [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Revegetation makes the land surface become covered by plant canopy, and the percentage of the cover becomes denser with the increasing age of the revegetated plants. As revegetation trees grow over time, the microclimate of the reclaimed sites also changes, as indicated by a lower light intensity on the ground, a lower air temperature, and a relatively higher humidity [65][66][67]. A more detailed explanation of revegetation activities can be found in Section 4.…”
Section: Revegetation Processmentioning
confidence: 99%
“…Suhu, kelembaban udara serta intensitas cahaya merupakan faktor lingkungan yang berpengaruh pada fase metamorfosis, pigmentasi sayap, adaptasi termal, perilaku kawin, perilaku bertelur dan mencari mangsa (Herlambang et al 2016;Svensson & Waller 2013). Keberadaan vegetasi pohon sangat berpengaruh pada suhu dan kelembaban udara pada ketinggian 2 meter di atas tanah (Procházka et al 2011). Selain itu keberadaan vegetasi pohon dengan kanopi juga mengurangi intensitas cahaya sehingga keberadaan pohon berpengaruh pada keanekaragaman Odonata.…”
Section: Gambar 2 Grafik Indeks Keanekaragamanunclassified